Sustainable Management Strategies Urban Water Bodies and Wetlands in the Indian Context (International Journal of Innovative Research in Engineering & Management, 2022)
The urban and peri-urban water bodies and  wetlands residing inside parks and the abundance of wildlife  they support are being threatened by intensive visits and  unexpected tourist and leisure activities in and around Indian  cities. Urban revitalization efforts often result in the gradual  devastation of local ecosystems. The major focus of this  thesis is on determining whether or not current management  approaches will secure the long-term viability of these  delicate ecosystems. Nature Park, Taratala, Kolkata;  Rabindra Sarobar, Kolkata; Eco Park, New Town, Rajarhat;  Jubilee Park, Gayshpur, Kalyani; and Millenium Science  Park, Ashoknagar, Habra were chosen as the five case study  locations in and around Kolkata, India. Scope The  fundamental goal of this study is to conserve urban and peri urban water bodies and wetlands, thus we will be looking at  the social, ecological, and economic sustainability of these  ecosystems. This study's focus is on water bodies and  wetlands within urban and peri-urban park settings, and it  uses socio-ecological criteria and indicators to analyze the  current state of five such case study sites. The study's goals  are to identify critical issues, the responsible and determining  factors of strengths and weaknesses at the case study sites,  and relevant policies at site and system levels.
Keywords: Urban Water Bodies; Wetlands; Sustainability